Microbiologically Induced Corrosion (MIC) of Carbon Steel in Biodiesel: a Comparative Analysis - Junaidi Junaidi; Tjandra Setiadi; Hary Devianto; Wolfgang Schmahl; Yustina Metanoia Pusparizkita (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The damaging process known as microbiologically influenced corrosion (MIC) can be triggered by the bioactivities of microorganisms. The occurrence of this phenomenon can be attributed to the presence of biodiesel in carbon steel diesel mixture storage tanks, since the biodegradability of the fuel promotes microbial development and the MIC process. In this work, the effects of different biodiesel concentrations (B0, B15, B20, B30, and B100) on biocorrosion in ST-37 carbon steel caused by three species were investigated. Some of the species confirmed to be involved are S. marcescens, B. megaterium and B. lichenisformis. These three species are undoubtedly able to survive in a biodiesel-based media. In addition to producing EPS, a species that may slow the rate at which carbon steel corrodes, biodiesel can be utilised as a supply of nutrients. Nonetheless, the diverse life cycles of microbes have the potential to accelerate corrosion of carbon steel. The average corrosion rate with the effect of B. lichenisformis is lower than the other two species, notably in the B100, with fewer colonies than S. marcescens and B. megaterium.Some of the species confirmed to be involved are S. marcescens, B. megaterium and B. lichenisformis.